2009
DOI: 10.1007/s00024-009-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Omori’s Law Applied to Mining-Induced Seismicity and Re-entry Protocol Development

Abstract: This paper describes a detailed study of the Modified Omori's law n(t) = K/(c ? t) p applied to 163 mining-induced aftershock sequences from four different mine environments in Ontario, Canada. We demonstrate, using a rigorous statistical analysis, that this equation can be adequately used to describe the decay rate of mining-induced aftershock sequences. The parameters K, p and c are estimated using a uniform method that employs the maximum likelihood procedure and the Anderson-Darling statistic. To estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…The p value statistic represents a power law aftershock decay rate as defined by the Modified Omori's law: Nitalict=italickt+cpwhere N ( t ) is the number of aftershocks per day, and k and c are constants [ Utsu , ]. This relation has been demonstrated to model aftershock decay rates observed for both naturally occurring and mining‐induced sequences of seismicity [ Vallejos and McKinnon , ]. A p value of 1.11 ± 0.06 (2 σ ) was computed for this catalog using ZMAP [ Wiemer , ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The p value statistic represents a power law aftershock decay rate as defined by the Modified Omori's law: Nitalict=italickt+cpwhere N ( t ) is the number of aftershocks per day, and k and c are constants [ Utsu , ]. This relation has been demonstrated to model aftershock decay rates observed for both naturally occurring and mining‐induced sequences of seismicity [ Vallejos and McKinnon , ]. A p value of 1.11 ± 0.06 (2 σ ) was computed for this catalog using ZMAP [ Wiemer , ].…”
Section: Resultsmentioning
confidence: 99%
“…A p value of 1.11 ± 0.06 (2 σ ) was computed for this catalog using ZMAP [ Wiemer , ]. According to Vallejos and McKinnon [], the median p value for 163 mining‐induced seismicity sequences observed in four Canadian hard‐rock mines was found to be 1.1, indicating close agreement. A prior study of seismicity at CCM found a p value of 0.8 ± 0.3 using only 15 events with M C > 1.6.…”
Section: Resultsmentioning
confidence: 99%
“…The locations of the aftershocks stay reasonably constant over a 2 day period, and no systematic migration patterns were observed. The time distribution of the aftershocks follows Omori's law with a p value of 0.48, which seems low but is reasonable in a mine setting [ Vallejos and McKinnon , ].…”
Section: Methodsmentioning
confidence: 99%
“…For longer time periods, those of interest in this study, it has been shown that the exponential decay predominates over power-law decay (Otsuka 1985(Otsuka , 1987Souriau et al 1982) for aftershocks. Also, the decay times in this study are in the order of weeks as opposed to hours or days for major events in mines (Vallejos and Mckinnon 2010;Olivier et al 2015). Furthermore, as no single earthquake in our sequences is a main shock but the result of weakly production in the mine, the process may have a closer relation to that of earthquake swarms as opposed to aftershocks (see e.g.…”
Section: Introductionmentioning
confidence: 71%